Application of high frequency biasing and its effect in STOR-M tokamak. (3rd August 2020) - Basu, Debjyoti; Nakajima, Masaru; Melnikov, A.V.; Martinell, Julio J.; McColl, David; Singh, Raj; Xiao, Chijin; Hirose, Akira
Abstract: A pulsed oscillating power amplifier has been developed to apply high frequency biasing voltage to an electrode at the edge of the STOR-M tokamak plasma. The power amplifier can deliver a peak-to-peak oscillating voltage ±60 V and current 30 A within the frequency range 1 kHz–50 kHz. The electrode is located in the equatorial plane at radius ρ  = 0.88. The frequency of the applied voltage has been varied between discharges. It is observed that the plasma density and soft x-ray intensity from the plasma core region usually increase at lower frequency regime 1 kHz–5 kHz as well as relatively higher frequency regime 20 kHz–25 kHz but seldom increase in between them. Increment of τ \! E has been observed 40% and 20% for the frequency regimes of 1 kHz–5 kHz and 20 kHz–25 kHz, respectively, and τ \! p increment is 25% for both frequency regimes. Transport simulation has been carried out using the ASTRA simulation code for STOR-M tokamak parameters to understand the physical process behind experimental observations at the higher frequency branch. The model is based on geodesic acoustic mode(GAM) excitement at resonance frequency associated with Ware-pinch due to the oscillating electric field produced by biasing voltage, which can suppress anomalous transport. Simulation results reproduce the experimental trends quite well in terms of the density, particle confinement, as well as energy confinement time evolution. All the results indicate that high frequency biasing is capable of improving confinement efficiently.